PENGENDALIAN KADAR GLUKOSA DARAH OLEH TEH HIJAU DAN ATAU TEH DAUN MURBEI PADA TIKUS DIABETES - Rusman Efendi; Evy Damayanthi; Lilik Kustiyah; Nastiti Kusumorini (Food and Nutrition Society of Indonesia, 2010)
Diabetes mellitus is degeneratif disease with high prevalence that happens in many countries. Several studies had been done to control diabetes by using green tea, mullberry leaf tea, and their mixture. The aim of this research was to analyze the influence of the administration green tea, mullbery leaf tea, and their mixtures to blood glucose level of diabetic rats both during 120 minutes after administration. This research had four phases, first to determine the best mullberry leaf tea, second to fourth phases respectively, determine turnover of blood glucose level on normal rats; attempt during 120 minutes on diabetic rats. The result of research during 120 minutes have showed that blood glucose level on diabetic rats which were administered by green tea, mullberry leaf tea and their mixture is significantly difference with diabetic rats which were administered by water. Blood glucose level at baseline increased at 30th minutes and showed the difference significantly and then until 60th and 120th minutes and relatively stable. During 120 minutes after feed consumption, inhibition of blood glucose level occured increasingly on diabetic rats which were administered by green tea, mullberry leaf tea, and their mixture compared to diabetic rats which were administered by water.